Three-dimensional response of steel moment-resisting buildings under seismic sequences. (15th November 2018) - Ruiz-García, Jorge; Yaghmaei-Sabegh, Saman; Bojórquez, Edén
Highlights: 3-D response of steel buildings under seismic sequences is different than 2-D response. Modeling approach of 3-D models influences the drift response under sequences. Angle of incidence of aftershocks have effect on the drift response of 3-D models. Response of 3-D models depended on the mainshock-aftershock ground motion features. Abstract: This study examines the response of three-dimensional (3-D) steel moment-resisting buildings having 3-, 9-, and 20-story height under bi-directional attack of real seismic sequences with different earthquake ground motion features. For this purpose, 3-D analytical models were developed for each building, which include or not include interior gravity frames. The fracture behavior in beams included in perimeter moment-resisting frames and the bending capacity of interior beams in gravity frames was taken into account in the modeling process. The seismic response of the 3-D building models, in terms of lateral interstory drift demands, was also compared with the response of their corresponding two-dimensional (2-D) bare frame model to highlight differences in modelling criteria. It is shown that differences among 2-D and 3-D building models depend on the type of seismic sequence. When differences arise, it is clearly illustrated that the 3-D building models experience different response than the 2-D model. Between the 3-D models, it is shown that the seismic response is different, with differences depending on the angle of incidence of the orthogonal components of the seismic sequences and the number of stories. This study demonstrates that the modelling approach in 3-D models has significant influence in seismic response of steel framed-buildings under seismic sequences.